EFFORTS FOR ESTABLISHING STUDENT'S RELIGIOUS CHARACTER THROUGH HABITIVE ACTIVITIES (DHUHA PRAYER, READING SURAT AL MULK, AND ASMAUL HUSNA) BEFORE LEARNING AT SMPIT IBNU KHALDUN PANAMBANGAN - Vivi Meilinda; Saona Saona; Rani Santika; Nur Alifah (Green Publisher, 2022)
This study aims to analyze the implementation of habituation, supporting and inhibiting factors faced in the implementation of Solau Dhuha habituation, reading Al-Mulk letter , reading Asmaul Husna, and sholawat in order to shape the religious character of students. This research is a qualitative research that systematically describes the facts found in the field. This research was conducted at SMPIT Ibnu Khaldun in Panambangan Village, Sedong Kab. Cirebon in the even semester of the 2021/2022 academic year. The subjects of this study were teachers, principals, homeroom teachers and seventh grade students. The focus of this research is what refractions are done and applied by teachers in the learning process at SMPIT IB as an effort to instill character education in students. Researchers used data collection techniques, namely by observation, interviews and documentation. The results found that: (1) forming a religious character by habituation of Dhuha Prayer and reading Al-Mulk, reading Asmaul Husna and Sholawat Nabi carried out before starting the lesson. (2) Factors supporting the application of the formation of students' religious character through habituation of Dhuha Prayer and reading Al-Mulk's letter , reading Asmaul Husna and Sholawat Nabi at SMPIT Ibnu Khaldun, namely: support from parents, good cooperation between school members, and adequate facilities . (3) the obstacles that exist in shaping the religious character of students through habituation of Dhuha Prayer and reading Al-Mulk's letter, reading Asmaul Husna and Sholawat Nabi at SMPIT Ibnu Khalsun are motivated by different student circumstances, lack of basics in students, and the environment or student engagement.